Cambodia : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cambodia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that economic activity in Cambodia remained strong with a growth rate at 7 percent in 2014, notwithstanding appreciation of the real effective exchange rate following U.S. dollar strengthening and growing competition from other low-cost garment producers. Inflation fell in 2014 and through 2015, owing to strong external disinflationary pressures from lower food and oil prices. The short-term outlook remains broadly favorable. Growth is projected to remain robust at 7 percent in 2015, while inflation is projected to rise gradually to about 2 percent by end-2015. The fiscal deficit is projected to rise modestly to 2 percent in 2015 as a result of strong measures to improve revenue administration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet